Synergism of Lecanicillium lecanii (Zimm) and Chromolaena odorata L. Leaf Extract to Control Aphis gossypii (Glover) in Chili Plants - Nurhayati, Wiwik; Haryadi, Nanang Tri (Graduate School, Universitas Brawijaya, 2022)
The purpose of the study was to determine the effect of the appropriate and effective application of the L. lecanii fungus and C. odorata L. leaf extract in increasing the mortality of A. gossypii. The study was divided into two stages. The first stage was in vitro test of L. lecanii synergism plus C. odorata L. leaf extract in PDA media with four treatments, namely LK0= L. lecanii 107 conidia.mL-1 plus 0% C. odorata L. leaf extract, LK1= L. lecanii 107 conidia.mL-1 plus 10% C. odorata L. leaf extract, LK2= L. lecanii 107 conidia.mL-1 plus 25% C. odorata L. leaf extract; LK3= L. lecanii 107 conidia.mL-1 plus 40% C. odorata L. leaf extract. The second stage was the toxicity test of the application of L. lecanii suspension and C. odorata L. leaf extract on mortality of A. gossypii. The toxicity test was based on the results of the synergism test, where the addition of C. odorata L. leaf extract to L. lecanii growing media showed incompatible results. Therefore, the toxicity test was carried out separately with five treatments, namely H0= Control (aqua dest); H1= Conidia suspension L. lecanii 107 conidia mL-1; H2= 10% C. odorata leaf extract; H3= 25% leaf extract of C. odorata; H4= 40% C. odorata leaf extract. The results showed that the compatibility test of L. lecanii with leaf extract of C. odorata L. was incompatible and classified as toxic. The addition of C. odorata L. leaf extract in concentrations of 10%, 25%, and 40% could significantly inhibit colony growth, sporulation, and conidia viability of L. lecanii, with a higher level of inhibition as the concentration of C. odorata L. leaf extract, was added. The toxicity test of a separate application of C. odorata L. leaf extract and L. lecanii suspension had a significant effect on mortality of 3rd instar nymph A. gossypii, with the highest mean mortality found in a single application of 40% C. odorata L. leaf extract with an average mortality of 100% at 96 HAA(Hours After Application) observations. Keywords: A. gossypii, C. odorata L. leaf extract, L. lecanii, synergism.